(untitled) (Salud, Arte y Cuidado, 2019)
Crouzon syndrome, known as craniofacial dysostosis, is a genetic disorder normally inherited with an autosomal dominant pattern that has a prevalence of one per 25,000 live births. This disorder is described as a craniofacial malformation, clinically presenting with craniosynostosis, facial dysmorphism, maxillary hypoplasia, mandibular prognathism, exophthalmia, hypertelorism and other associated anomalies. It is caused by a mutation in the FGFR2 gene that encodes Receptor 2 of the Fibroblast Growth Factor, located on the chromosome 10. We present the autopsy of a male fetus, 19 weeks old, of a healthy mother, aged 31 years and with no family history, who presented the anatomical and pathological findings compatible with the Crouzon Syndrome. The objective of this case is to present these findings found during the fetal autopsy, to give a diagnosis of the syndrome, as well as provide enriching information for the medical literature.